Firm wage adjustment across position during Covid-19 crisis - Azhar, Azim; Yong, Chen Chen (Journal of Islamic, Social, Economics and Development, 2025)
The COVID-19 pandemic has disrupted the global economy, compelling firms to adapt and make crucial decisions for their business survival. Firms experienced unparalleled difficulties stemming from social distancing regulations, lockdowns, and travel restrictions that significantly affecting productivity, supply chains, and customer demand. In this uncertainty times, firms were compelled to make crucial decisions to ensure their business continuation, including adjustments to wages as part of their business strategic planning. This paper explores how firm’s implements wage adjustments as a strategy for company continuation including the effects of wage reductions differ among various positions in Malaysia. This study offered insights into wage adjustments across positions based on data extracted from the National Job Portal, My Future Job. This study will extend the existing literature by providing evidence on how wage adjustment differs across firms. Findings of this study will fill an important gap in the existing literature by providing evidence and information on the wage adjustment implementation by firms in Malaysia across positions.